Corpus linguistics and the web: [papers presented at the symposium Corpus Linguistics - Perspectives for the Future that was held at the IWH (Internationales Wissenschaftsforum) in Heidelberg in October 2004] - Hundt, Marianne; Nesselhauf, Nadja; Biewer, Carolin (Language and computers, 2007)
'He rung the bell' and 'she drunk ale' -- non-standard past tense forms in traditional British dialects and on the internetDiachronic analysis with the internet? Will and shall in ARCHER and in a corpus of e-texts from the web.
In part, contributions to a conference entitled: Corpus Linguistics -- Perspectives for the future, held in Heidelberg in October 2004. - Conference organized by the Internationales Wissenschaftsforum Heidelberg (IWH), Fritz Thyssen Stiftung and Stiftung Universität Heidelberg. - Includes bibliographical references and index. - Description based on print version record
Keywords: Electronic books; Electronic books -- Conference proceedings; Konferenzschrift; Aufsatzsammlung; World Wide Web; Korpus; Internet; Englisch